Mitigando Ataques de Negação de Serviço em Infraestruturas de Computação em Nuvem. - MEDEIROS, Gleison de Oliveira (2014)
Cloud computing has been widely used as an ultimate solution for the growing demands of users of Information Technology services. Concomitant to the rapid development of this technology, new forms of intrusion (and intruders) have emerged. In this context, it is proposed in this dissertation, an architecture of intrusion detection system based on Multi-agent systems associated with the use of techniques for encryption and digital signature to detect and treat the attempted denial of service attacks in an Infrastructure Service. The partial results obtained with the implementation of a prototype are considered satisfactory in view of the performance presented by the tool.